Analisis Pengaruh Service Quality Digital Banking Wokee Dan Customer Experience Terhadap Customer Satisfaction Bank Bukopin - Syahfitri, Delviranti; Oktarici, Eddo Nanda (Pusat P2M Politeknik Negeri Batam, 2024)
Wokee is a fintech application that was established in 2017. Nevertheless, company entities persistently pursue innovation and expansion by incorporating features and advantages that can be fully utilised by KB Bukopin customers. The public's need for convenient financial services and the gradual shift of transactions to the digital domain have given rise to several financial enterprises that are actively expanding their digital operations. This study investigates the operations and activities of PT Bank Bukopin KCU Nagoya Branch. The research utilised a national sample of approximately 100 respondents, obtained through the WOKE survey. The researchers utilised data processing software tools, specifically SPSS Version 25. The research findings demonstrated a direct and substantial impact of service quality on consumer satisfaction. The customer experience has a substantial impact on consumer satisfaction. The quality of service and customer experience have a simultaneous impact on customer satisfaction at Bank Bukopin KCU Nagoya Batam branch.